Hybridization and polyploidization effects on LTR‑retrotransposon activation in potato genome - Gantuz, Magdalena; Morales Sanfurgo, Hugo Andres; Bertoldi, Maria Victoria; Ibañez, Verónica Noé; Duarte, Paola Fernanda; Marfil, Carlos Federico; Masuelli, Ricardo Williams (The Botanical Society of Japan, 2021)
Hybridization and polyploidization are major forces in plant evolution and potatoes are not an exception. It is proposed that the proliferation of Long Terminal Repeat-retrotransposons (LTR-RT) is related to genome reorganization caused by hybridization and/or polyploidization. The main purpose of the present work was to evaluate the effect of interspecific hybridization and polyploidization on the activation of LTR-RT. We evaluated the proliferation of putative active LTR-RT in a diploid hybrid between the cultivated potato Solanum tuberosum and the wild diploid potato species S. kurtzianum, allotetraploid lines derived from this interspecific hybrid and S. kurtzianum autotetraploid lines (ktz-autotetraploid) using the S-SAP (sequence-specific amplified polymorphism) technique and normalized copy number determination by qPCR. Twenty-nine LTR-RT copies were activated in the hybrid and present in the allotetraploid lines. Major LTR-RT activity was detected in Copia-27, Copia-12, Copia-14 and, Gypsy-22. According to our results, LTR-RT copies were activated principally in the hybrid, there was no activation in allotetraploid lines and only one copy was activated in the autotetraploid.